Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
To integrate csc^2(x)cot(x), use u-substitution with u = csc(x).
To integrate csc^2(x)cot(x), we can use u-substitution with u = csc(x). This means that du/dx = -csc(x)cot(x)dx, which can be rearranged to give -du = csc(x)cot(x)dx. Substituting this into the integral gives:
∫csc^2(x)cot(x)dx = ∫-u^-2du
Integrating this gives:
∫csc^2(x)cot(x)dx = u^-1 + C
Substituting back in for u gives:
∫csc^2(x)cot(x)dx = csc(x) + C
Therefore, the integral of csc^2(x)cot(x) is csc(x) + C.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.